Cell Deformation at the Air-Liquid Interface Evokes Intracellular Ca2+ Increase and ATP Release in Cultured Rat Urothelial Cells - Wen, Jiliang; Chen, Zhenghao; Zhao, Mengmeng; Zu, Shulu; Zhao, Shengtian; Wang, Shaoyong; Zhang, Xiulin (Frontiers in Physiology, 2021)
Bladder urothelial cells have been implicated in bladder mechanosensory transduction. Cell deformation caused by tension forces at an air-liquid interface (ALI) can induce intracellular Ca2+ concentration ( [Ca2+]i) increase and ATP release in some epithelial cells. In this study, we aimed to examine the cellular mechanisms underlying ALI induced [Ca2+]i increase in cultured urothelial cells. ALI was created by stopping the influx of the perfusion but maintaining efflux. [Ca2+]i increase were measured using Ca2+ imaging method. ALI evoked reversible [Ca2+]i increase and ATP release in urothelial cells, which was almost abolished by GdCl3. The specific antagonist of TRPV4 channel (HC0674) and the antagonist of pannexin-1 channel (10panx) reduced [Ca2+]i increase, respectively. The blocker of Ca2+-ATPase pumps on ER (Thapsigargin), IP3 receptor antagonist (Xest-C), ryanodine receptor antagonist (ryanodine) reduced [Ca2+]i increase, respectively. Degrading extracellular ATP with apyrase, or blocking ATP receptors (P2X or P2Y) with PPADS significantly reduced [Ca2+]i increase. Our results suggest that both Ca2+ influx via TRPV4 or pannexin-1 and Ca2+ release from intracellular Ca2+ store via IP3 or ryanodine receptors contribute to mechanical responses of urothelial cells. ATP release further enhance [Ca2+]i increase by acting P2X and P2Y receptors via autocrine or paracrine mechanisms.